Effects of Protein and Supplemental Fat on Performance of Laying Hens - Wu, Y.Z.; Zou, Shi Geng (International Journal of Poultry Science, 2005)
A 2 x 2 factorial experiment of two protein levels (17.0 and 15.9%) with and without supplemental fat was conducted to determine the effect of supplemental fat on performance of commercial Hy-line W-36 at different protein levels from 47 to 55 week of age. Hens at 47 week of age were randomly assigned into 4 treatments (6 replicates of 15 birds per treatment). There were no significant interactions between protein and supplemental fat in feed intake, egg production, egg weight, egg mass, feed conversion, egg specific gravity, and body weight. Protein had significant effects on egg production, egg mass, and feed conversion, but had no effect on feed intake, egg weight, egg specific gravity, and body weight. With increasing protein level, egg production and egg mass significantly increased and feed conversion significantly decreased. Supplemental fat had no effect on egg production, egg weight, egg mass, and body weight. Supplemental fat significantly reduced feed intake and improved feed conversion at both protein levels. Supplementing fat in diets can improve performance of commercial Hy-line W-36.